Changes in household food security, nutrition and food waste along an agro-ecological gradient and the rural-urban continuum in mid-sized South African towns - Chakona, Gamuchirai (Rhodes University, Faculty of Science, Department of Environmental Science, 2017)
The lack of dietary diversity is a severe problem experienced by most poor households globally. Most poor communities are at high risk of inadequate intake of micronutrients resulting from diets dominated by starchy staples. The present study considered the diets, dietary diversities and food security of women of reproductive age between 15-49 years, households and communities along the rural-urban continuum in three mid-sized towns situated along an agro-ecological gradient in South Africa. A 48-hour dietary recall was performed across two seasons (twice in summer and once in winter) and focus group discussions were held to gather all information including food abundance, seasons of food scarcity as well as coping strategies which households employ during periods of food shocks. Households were further asked to quantify any type of food waste that they could have generated in the previous 48 hours. Nutritional status of children under the age of five in all three towns was also measured using height-for-age (HAZ) and mid-upper arm circumference (MUAC) as indicators of stunting and wasting respectively. The household surveys were conducted with 554 women randomly selected in rural, peri-urban and urban locations of Richards Bay, Dundee and Harrismith. For nutritional status, the sample consisted of 216 children who were randomly selected from the sampled households in rural, peri-urban and urban locations of the study sites. Household Dietary Diversity Scores (HDDS) and Women's Dietary Diversity Scores (WDDS) were calculated from the food items consumed by each household and each woman over a two-day period, respectively. Household food access was also measured for each household using Household Food Insecurity Access Scale (HFIAS). The mean WDDS and HDDS for the wettest site of Richards Bay (3.8±0.29 and 8.44±1.72, respectively) was significantly higher than at Dundee (3.4±0.30 and 7.76±1.63, respectively) and Harrismith (3.5±0.27 and 7.83±1.59, respectively) which were not different from one another. The mean HFIAS for Dundee (9.39±7.13) was significantly higher than that in Richards Bay (5.57±6.98) and Harrismith (6.43±6.59) which were not significantly different from one another. Dietary diversity scores were also significantly higher in urban locations than in peri-urban and rural ones whilst HFIAS was significantly lower in the urban locations than peri-urban and rural locations. There was lower dependence on food purchasing in Richards Bay compared to Dundee and Harrismith where the majority of the population was purchasing most of their food. The majority of Richards Bay households were involved in subsistence agriculture and also produced a surplus for sale, as well as collecting wild foods, which improved food security, unlike Dundee and Harrismith. Food insecurity was higher in rural and peri-urban areas compared to urban areas. In all towns, food was always available throughout the year but was beyond the reach of many households. In urban areas food was readily available and only limited by access, whereas rural populations have limited access to affordable food and face higher prices. The peri-urban populations were more food insecure because of high levels of poverty, unemployment and lack of access/entitlements to land. Periurban dwellers are therefore more sensitive to changes in incomes and food prices because they lack safety nets to absorb income or price shocks as they purchase more, rather than growing their own food. Household dietary diversity was significantly negatively correlated with household food access, that is households with low HDDS had higher HFIAS scores. Due to high levels of food insecurity, a greater percentage of children under the age of five years were stunted (35 %) and wasted (18 %). There were no significant differences in stunting along the agro-ecological gradient, along the rural-urban continuum and sex of child. However, significant differences were observed in child wasting along the agro-ecological gradient with Harrismith having more wasted children than the other two towns, which were not significantly different from each other. Significant differences were also observed between MUAC and sex of child where male children had higher MUAC than females. Wasting was significantly negatively associated with HDDS, with children from households with low HDDS tending to have large MUAC thus showing an inverse association among HDDS and obesity. However, further studies are needed to confirm this finding. In general food insecurity was closely associated with low wealth, food expenditure, large household size and limited access to land. The study did not find any significant role in the use of wild foods and social grants in improving food security for those households who were consuming wild foods and those receiving social grants. Although a greater percentage of households were food insecure, significant amounts of unprepared food (495±179 g per household) were wasted in Richards Bay alone in 48 hours mainly because the food had passed the best before date or had visibly gone bad. The amount of food waste was closely significantly negatively associated with household size. In general, the prevalence of food insecurity and wasting followed the agro-ecological gradient, with households in Richards Bay where the area.
Keywords: Food security -- South Africa; Women -- South Africa -- Nutritiona; Urban women -- South Africa -- Nutrition; Rural women -- South Africa -- Nutrition; Wild foods -- South Africa; Food supply -- South Africa; Malnutrition in children -- South Africa; Grants-in-aid -- South Africa; Household ecology -- South Africa